"Nothing to offer in return": Refugees, human rights, and genocide in Cambodia, 1975–1979. (June 2020) - Madokoro, Laura
From 1975 to 1979, Canadian politicians and diplomats observed and discussed the possibility that a genocide was taking place in Cambodia. The situation was difficult to ascertain, however, given the limited history between the two countries and the deep isolation in which the Khmer Rouge regime operated after rising to power, as well as the Canadian government's limited interest in international human rights until the late 1970s. It wasn't until large numbers of refugees began to cross into Thailand in 1977–78, and began to tell their stories to Western diplomats, that human rights discussions at the United Nations began to focus more closely on the situation in Cambodia. Exploring the Canadian government's use of refugee testimonies, this article explores the relationship between narratives of mass violence and the burgeoning human rights agenda of the late 1970s to highlight the role of refugees in shaping an international human rights agenda.